PENDIDIKAN ANAK DALAM PERSPEKTIF GENDER (STUDI KASUS PENDIDIKAN ANAK DI DESA KALIPANG KECAMATAN GRATI KABUPATEN PASURUAN) - Iwantoro Iwantoro (JIE (Journal of Islamic Education), 2019)
This study aims to determine the perceptions or opinions of parents or the community about children's education between girls and boys. In addition, it also reviews the factors that cause gender irregularities in children's education. This study used qualitative research by taking the location or object of research in Kalipang Village, Grati District, Pasuruan Regency, the informants were community members, community leaders, and village heads. The results of the study show that gender deviations occur in education, which means that parents or the community have a tendency to boys rather than girls in the field of education. Boys get more opportunities to get higher education than girls. The factors that cause gender irregularities are 1) relatively low level of community education, 2) relatively low economic level, 3) community stereotypes that regard women as weak creatures, and 4) social and cultural life in society that places women as beings whose activities are very limited.